220k views
0 votes
Ln x + ln (x + 1) = ln 56

User Ebikeneser
by
5.8k points

1 Answer

1 vote

Answer:

Reorder the terms:

ln(-1 + x) + ln(x) = ln(56)

(-1 * ln + x * ln) + ln(x) = ln(56)

(-1ln + lnx) + ln(x) = ln(56)

Multiply ln * x

-1ln + lnx + lnx = ln(56)

Combine like terms: lnx + lnx = 2lnx

-1ln + 2lnx = ln(56)

Reorder the terms for easier multiplication:

-1ln + 2lnx = 56ln

Solving

-1ln + 2lnx = 56ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-56ln' to each side of the equation.

-1ln + -56ln + 2lnx = 56ln + -56ln

Combine like terms: -1ln + -56ln = -57ln

-57ln + 2lnx = 56ln + -56ln

Combine like terms: 56ln + -56ln = 0

-57ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.

ln(-57 + 2x) = 0

Explanation:

User Nenette
by
5.1k points